PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KINERJA PERUSAHAAN(STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA PADA TAHUN 2010 DAN 2011) - Helen Octavia; Hermi Hermi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2014)
The purpose of this research is to test the effect of CSR on firm financial and market performance. This research used Corporate Social Disclosure Index (CSDI) as a measure of CSR disclosure, based on indicators from Research Based. The samples of this research are 56 public firms manufacture listed in Indonesian Stock Exchange (IDX) year 2010 and 2011. Relatively lower score of CSDI shows that CSR disclosure in firms’ annual report is still low. This may due to there is still no mandatory rules regarding CSR disclosure in Indonesia and the lack of firms’ awareness of the importance of CSR and its disclosure in annual report. Test results show that CSR disclosure have positive and significant effect on Return on Asset as a measure of financial performance, but CSR disclosure do not has significant effect on cumulative abnormal return (CAR) as a measure of market performance.